’n Kritiese beskouing van woordeboeke met geamalgameerde lemmalyste - Prinsloo, D.J. (Lexikos, 2013)
A Critical Examination of Dictionaries with Amalgamated Lemmalists. The recently published Groot Woordeboek (Afrikaans en Nederlands), also known as ANNA, is the first dictionary with an amalgamated lemmalist based on the model of Martin and Gouws (2000). ANNA also paves the way for a similar approach for other closely related languages such as the Sotho languages and the Nguni languages of South Africa. The advantages and disadvantages of five aspects namely (a) comparison and contrast, (b) user-friendliness, (c) space saving, (d) ordering of senses and (e) provision of a separate grammatical compendium are critically evaluated. The principles of amalgamation, the relevant lemma types, as well as certain characteristics of the model are briefly discussed beforehand.